Histological Findings in Ruptured Aneurysms Treated with GDCs: Six Examples at Varying Times after Treatment - Groden, Christoph; Hagel, Christian; Delling, Guenter; Zeumer, Hermann (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: A novel plastic embedding approach was used to histologically evaluate inflammatory changes and scar formation over time and to better visualize the mesh attenuation within the aneurysm lumen of acutely ruptured aneurysms after treatment with GDCs.METHODS: Autopsies were performed on six patients with acute subarachnoid hemorrhage who had died between 5 and 272 days after GDC treatment. The aneurysms containing the platinum coils were embedded in plastic along with the intact parent vessels, were sliced, and were ground to a thickness of 5 to 10 μm. In addition, 250-μm-thick sections were prepared. Histologic examinations were performed. Three exemplary cases representing the time lapse from treatment to death are discussed in detail.RESULTS: At the three exemplary time periods (5, 13, and 272 days) after coiling, a continuing healing process could be observed. At 5 days after placement of GDCs, a blood clot consisting of erythrocytes and fibrin was found throughout the cavity. Thirteen days after the procedure, large foamy macrophages were observed near the coils in the aneurysm cavity. Two hundred seventy-two days after the intervention, scar formation within the aneurysm appeared to be completed, with vascularized connective tissue filling the cavity and embedding the coils. Large foreign body giant cells were found adjacent to the coils. A layer of long slender cells, resembling endothelium, sealed the aneurysm neck.CONCLUSION: We postulate that within days after GDC treatment, blood clotting and thrombus formation prevent rebleeding and that solid scar formation covered by a layer of long slender cells, resembling endothelium, seals the aneurysm over time.